Advances in accounting behavioral research. 24 - Karim, Khondkar E., 1961- (Emerald Publishing Limited, 2021)
Advances in Accounting Behavioral Research is a publication of emerging theory, methods, and practical applications for behavioral research within accounting and auditing. It is dedicated to promoting peer-reviewed research that spans all facets of accounting behavioral research, including but not limited to: applied psychology, sociology, management science, ethics, and economics. In so doing, it provides a unique, interdisciplinary forum for the discussion, development, and expansion of theories within these related subjects. This 24th volume features five papers from experts writing on accountability pressure and budgetary slack, whistle-blowing, limited attention, audit quality and auditor responsibility, and psychological contracts. Working on both the individual and organizational level, it is essential reading for accounting students and educators, with valuable insights on practice for those working in the field.